Cortical border-zone infarcts: clinical features, causes and outcome. Issue 8 (13th June 2012) - Joinlambert, Claire; Saliou, Guillaume; Flamand-Roze, Constance; Masnou, Pascal; Sarov, Mariana; Souillard, Raphaelle; Saliou-Théaudin, Marie; Guedj, Thierry; Assayag, Patrick; Ducreux, Denis; Adams, David; Denier, Christian
Abstract : Objective: To report the clinical features, causes and outcome of cerebral cortical border-zone infarcts BZI (C-BZI). Methods: The authors prospectively included patients with MRI-confirmed C-BZI among individuals consecutively admitted in Stroke Unit. Results: Forty-five patients presented C-BZI out of 589 with MRI-confirmed cerebral infarcts (7.6%). Particular clinical characteristics existed in C-BZI in comparison with other cerebral infarctions as a whole, including: (1) frequent transient symptoms at onset (27% vs 9%; p<0.001) and low severity score (NIHSS=3.1±3.0 vs 5.2±6.1; p=0.02); (2) early seizures in first 2 weeks (7/45 (15.6%) vs 12/544 (2.2%); p<0.001), even when focusing only on other infarctions involving the cerebral cortex (15.6% vs 4.3%; p<0.01); (3) heterogeneous clinical presentation but specific transcortical aphasia allowing a clinical suspicion of BZI before MRI; and (4) frequently associated internal carotid disease (69%), with subsequent early surgery in 75% of the cases. Following adapted care in stroke unit, C-BZIs' prognosis appeared good (Rankin score ≤2 at D90) for 82% of the patients. Conclusion: Some clinical features are overrepresented in such infarctions, including initial transient symptoms preceding the onset of a completed deficit, transcortical aphasia and early seizures. Despite lower initial severity, C-BZIs justify early management in stroke unit, often followed by carotid surgery, leading to an overall good prognosis.